Design of Helical Type Steam Generator for Experimental Power Reactor – Helium Side - Putri, Sunny Ineza; Subekti, Mohammad; Martin, Awaludin; P, Brian Agung Cahyo; Hermanto, Jheri; Siregar, Ansor Salim (Piston: Journal of Technical Engineering, 2025)
Previous research has not analyzed the helium temperature distribution in the RDE steam generator shell. This study aims to fill that gap by analyzing these thermal characteristics with empirical calculations and Ansys Fluent simulations. The validity of the RDE steam generator design is reaffirmed, having been successfully analyzed from both the water-flow perspective in previous research and the helium-side perspective in the present study. The analytical methods used herein showed strong consistency, with empirical and numerical simulation results differing by less than 10% across all parameters. Although the calculated shell height of 5.73 m exceeds the RDE design's 4.97 m, the overall design's validity is confirmed.